CEO Tenure and Performance: A case study of Arsène Wenger at Arsenal Football Club 1996-2018. - Green, Joshua (2018)
This study examines the relationship between CEO tenure and performance through utilising a case study of Arsène Wenger’s tenure. The aim is to examine the factors, themes and conditions which underpin an inverted U relationship between tenure and performance as posited by prior literature. The use of a case study provides an in-depth examination of how and why performance changes throughout a CEO’s tenure whilst allowing for context and underlying factors to be considered. Subsequently, this study seeks to extend prior literature through examining additional factors such as a CEO’s entry conditions and their restrictions, along with examining this phenomenon over a CEO’s entire career.